Kidney Stones - What should You know? - Szymańska, Ewa; Ostaszewska, Sandra; Świąder, Kinga; Augustynowicz, Kinga; Chrzanowski, Jakub (Journal of Education, Health and Sport, 2023)
Introduction: Kidney stones are mineral deposits in the renal calyces and pelvis that are found free or attached to the renal papillae. The risk of developing kidney stones is 10 to 15 percent in the United States and Europe, although this number is trending higher. Contributing risk factors for kidney stones are obesity, insulin resistance, gastrointestinal pathology, living in warmer climates, certain dietary patterns and medications. In this article we reviewed the epidemiology, symptoms and treatment of acute and chronic kidney stones and also prevention of stones formation in urinary tract. Material and methods: The work was based on medical articles collected in PubMed, websites and medical books. The research was conducted by looking at keywords such as: "Kidney Stones", "Renal Colic" and “Rirs”. Conclusions: The interdisciplinary approach, education of the patient and multiple endourological techniques can provide us with many solutions in the treatment of this contition. Doctors should adjust treatment to provide the best therapeutic effects.